Analysis of Items Parameters on Work and Energy Subtest Using Item Response Theory - Saepuzaman, Duden; Haryanto, Haryanto; Istiyono, Edi; Retnawati, Heri; Yustiandi, Yustiandi (Jurnal Pendidikan MIPA, 2021)
This study aims to describe the Physics test item parameters in Work and Energy and describe students’ abilities using the item response theory approach (IRT) dichotomous scoring. This research is quantitative descriptive. The research subjects were 1175 high school class XI students in West Java and Banten provinces consisting of 450 male students and 725 female students. The instrument used was Physics of Work and Energy as many as 25 items in multiple choices with dichotomous scoring. Student response data with dichotomous scoring were analyzed using the item response theory approach using the BILOG-MG program. The results showed that most of the items fit the 2PL model. Subsequent analysis of the items’ characteristics indicates that all items have different power and a level of difficulty in the good criteria. Keywords: item parameters, item response theory, physics test. DOI: https://dx.doi.org/10.23960/jpmipa/v22i1.pp1-9